2015
DOI: 10.1111/modl.12275
|View full text |Cite
|
Sign up to set email alerts
|

Oral Proficiency Assessment of English‐Proficient K–8 Spanish Immersion Students

Abstract: This cross‐sectional study used assessments developed by the Center for Applied Linguistics to examine the oral proficiency of 218 K–8 English‐proficient students in 4 Spanish immersion programs. Following a comprehensive review of assessment results for English‐proficient immersion learners, the article reports findings from statistical analyses. Ratings of student proficiency were significantly higher between Kindergarten and Grade 2 and between Grades 2 and 5; however, no significant differences were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 28 publications
5
48
0
Order By: Relevance
“…Rather consistently, studies have found that speaking scores tend to be lower than the receptive skills and, also, that they vary widely, a finding reported for secondary and postsecondary studies as well. Studies that were conducted on a smaller scale found that students achieved at the upper Intermediate range by fifth grade (e.g., Fortune & Tedick, ; Xu et al, ). In contrast, Burkhauser and her colleagues (), who conducted a district‐wide study, reported achievement of Intermediate High generally no earlier than eighth grade.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather consistently, studies have found that speaking scores tend to be lower than the receptive skills and, also, that they vary widely, a finding reported for secondary and postsecondary studies as well. Studies that were conducted on a smaller scale found that students achieved at the upper Intermediate range by fifth grade (e.g., Fortune & Tedick, ; Xu et al, ). In contrast, Burkhauser and her colleagues (), who conducted a district‐wide study, reported achievement of Intermediate High generally no earlier than eighth grade.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, Burkhauser and her colleagues (), who conducted a district‐wide study, reported achievement of Intermediate High generally no earlier than eighth grade. Studies that tracked DLI students’ proficiency levels into middle or high school (e.g., Burkhauser et al, ; Fortune & Tedick, ) found that proficiency gains tended to slow down or even decline in grades 7 and 8. The results for middle school grades are somewhat sobering, but not surprising, considering that instructional time in the immersion partner language typically declines from at least half of a school day in elementary grades, to no more than about 30% in middle school.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regardless of the assessment instrument used, most findings show that ratings of speech samples in L2 Spanish of EHL learners in DLI/TWI increased from one grade level to the next, indicating positive growth in proficiency (Burkhauser et al, 2016; Watzinger‐Tharp, Rubio, & Tharp, 2018). Results also suggest that EHL learners attained lower levels in oral proficiency than in reading and listening (Fortune & Tedick, 2015; Watzinger‐Tharp et al, 2018). Other studies, however, show limited development in L2 proficiency by EHL learners in DLI/TWI settings (Potowski, 2007a; Stipek, Ryan, & Alarcon, 2001; Tedick & Young, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The vast majority of studies have focused on the academic progress and achievement of students on content‐based, district and/or standardized tests in English, or on the overall L2 proficiency levels students attain across grade levels (Carranza, 1995; Christian, 1996; Downs‐Reid, 2000; Essama, 2007; Fortune, 2001; Genesee, 1987, 2004; Lindholm‐Leary, 2001; Potowski, 2007a, 2007b; Turnbull, Lapkin, & Hart, 2001). Few studies have explored, in depth, the linguistic features that characterize Second Language Acquisition (SLA) in English by language‐minority children (Potowski, 2007a, 2009); even less is known about L2 development in the partner language by EHL students (Fortune & Song, 2016; Fortune & Tedick, 2015; Tedick & Young, 2016). Research on L2 acquisition processes and development in the partner language within TWI contexts is necessary to gain a deeper understanding of how these programs progress.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a number of studies have pointed out that both native speakers of English (e.g., Marian, Shook, & Schroeder, ; Padilla, Fan, Xu, & Silva, ; Steele et al, ) and nonnative speakers (e.g., Lindholm‐Leary & Block, ; Marian et al, ; Steele et al, ; Thomas & Collier, ) can reach high levels of academic achievement when they are assessed in English on standardized (national, state, and/or district) assessments. Although less extensive, there has also been research proving the linguistic benefits of immersion programs (Burkhauser et al, ; Fortune & Tedick, ; Padilla et al, ; Watzinger‐Tharp & Rubio, ) and the positive effect that immersion programs can have on students' motivation and attitudes toward college as well as their academic success (Lindholm‐Leary & Borsato, ).…”
Section: Looking Forwardmentioning
confidence: 99%